The Mysticism of Sound and Music - Inayat Khan (Boston Shambhala, 1996)
Music, according to Sufi teaching, is really a small expression of the overwhelming and perfect harmony of the whole universe$1 (Band that is the secret of its amazing power to move us. The Indian Sufi master Hazrat Inayat Khan (1882-1927), the first teacher to bring the Islamic mystical tradition to the West, was an accomplished musician himself. His lucid exposition of music's divine nature has become a modern classic, beloved not only by those interested in Sufism but by musicians of all kinds.s
Include Notes and Index.
The Sufi Teaching of Hazrat Inayat Khan.
Keywords: Language and languages--Religious aspects -- Sufi literature -- Sufi music -- Music